ТРАНСФОРМАЦІЯ УПРАВЛІНСЬКИХ ПІДХОДІВ В ОРГАНІЗАЦІЯХ ПУБЛІЧНОГО СЕКТОРУ КРІЗЬ ПРИЗМУ ТЕОРІЇ X І Y Д. МАКГРЕГОРА - Марина Назаренко (Публічне управління і право: історія, теорія, практика, 2026)
The article explores the transformation of management approaches within public administration bodies through the lens of Douglas McGregor’s Theory X and Theory Y. It is substantiated that under the conditions of digitalization, crises, uncertainty, and rapid societal changes, the traditional model primarily grounded in control requires supplementation with human-centric and adaptive approaches. The study reveals the interconnection of Theory Y with trust, professional autonomy, intrinsic motivation, moral management methods, employee participation in decision-making, and the development of organizational culture. Using the examples of Prozorro and public participation mechanisms, it demonstrates that public governance performance can be ensured through the interaction of the state, employees, citizens, business, and other stakeholders. A conceptual Y+ model is proposed as a further evolution of Theory Y management logic. Unlike Model X, which focuses on control and compliance, and Model Y, which is rooted in trust, autonomy, and responsibility, Y+ emphasizes the co-creation of managerial decisions and public value. The sequence of managerial transformation («control → trust → co-creation») is defined, within which an employee transitions from an executor to a professional and co-creator, a manager shifts from a controller to a leader and facilitator, and a citizen moves from a service recipient to an active participant in creating public value. It is substantiated that Y+ does not imply the abandonment of control, but rather transforms it into output-based control (control by results) combined with professional autonomy, mutual accountability, and focus on societal outcomes. In such an environment, information, competencies, initiative, and the experience of various participants are regarded as a shared resource for solving societal issues and enhancing the quality of managerial decisions. This creates prerequisites for increasing organizational adaptability, bolstering trust in public authority, and ensuring its resilience amid uncertainty. The proposed approach can serve as a conceptual framework for developing adaptive, resilient, and human-centric public administration.